2014
DOI: 10.1080/17429145.2014.954014
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a mealybug infestation on the activity of amino acid decarboxylases in orchid leaves

Abstract: Changes in the activity of lysine decarboxylase (LDC), tyrosine decarboxylase (TyDC), and ornithine decarboxylase (ODC) within orchid (Phalaenopsis × hybridum 'Innocence') leaves, infested by two mealybug species: Pseudococcus longispinus (Targ. Tozz.) and Pseudococcus maritimus (Ehrh.) were quantified. The pattern of changes was dependent on the insect species and duration of infestation. P. longispinus feeding increased LDC and TyDC activity after one week during the total period of observations. This specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The nutrient solution was prepared by dissolving 60 g of the fertilizer in 60 L reservoir with tap water, and each plant was hand-fed with 500 mL every week. After two weeks, all experimental plants were infested with female adult mealybugs (30 per plant) by transferring insects onto plants using a soft brush [ 51 ]. Plants in test and control treatments were inoculated for a second time by drenching with a suspension of 200 mL B. bassiana at 1 × 10 8 conidial mL −1 in 0.01% Tween 80 and 0.01% Tween, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The nutrient solution was prepared by dissolving 60 g of the fertilizer in 60 L reservoir with tap water, and each plant was hand-fed with 500 mL every week. After two weeks, all experimental plants were infested with female adult mealybugs (30 per plant) by transferring insects onto plants using a soft brush [ 51 ]. Plants in test and control treatments were inoculated for a second time by drenching with a suspension of 200 mL B. bassiana at 1 × 10 8 conidial mL −1 in 0.01% Tween 80 and 0.01% Tween, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…However, TAL activity was elevated only in strawberry, and the change was significant after 5 h, 1 day and 2 weeks of mite feeding. Our earlier studies (Sempruch et al 2014) proved that some amino acid decarboxylases are also involved in orchid responses towards mealybugs infestation. It may suggest that regulation of amino acid accumulation in insect-infested plant tissues has a complex character and different biochemical agents may participate in this response.…”
Section: Discussionmentioning
confidence: 99%
“…)- Blackmer and Byrne (1999), Sandström et al (2000), and Sempruch et al (2011). Moreover, Sempruch et al (2012Sempruch et al ( , 2014 reported that the activity of some enzymes involved in different steps of amino acid biosynthesis and their further metabolism was also altered by aphid feeding. Proteomic analysis of biochemical changes in Pisum sativum (L.) infested by the pea aphid showed that the resistant pea cv.…”
Section: Introductionmentioning
confidence: 99%
“…The downregulation of arginine decarboxylase in transcriptomic data here depicts its role in disease susceptibility. Amino-acid decarboxylase gene exhibit suppression under sap-sucking insects and viral stresses [54, 55], therefore, we found this gene to be downregulated by whitefly and CLCuD stress response. Upregulation of CDF3 denotes its probable role in disease stress response as observed previously in pepper upon infection with different viruses [56].…”
Section: Resultsmentioning
confidence: 96%